Analisis Makna Quarter Life Crisis Dalam Lirik Lagu Bts “Zero O’clock” (Kajian Semiotika Ferdinand De Saussure) - Wardani, Indah Kusuma; Yuwono, Andri Prasetyo (Peneliti.net, 2024)
Music is part of communication, through song lyrics the communicator tries to convey a message to the communicant. If you look at the lyrics, music is a form of verbal communication. BTS (Beyond The Scene) or also often known as Bangtan Sonyeondan, is a male singer group from South Korea. BTS is one of the singers who uses music as a medium for conveying messages to their listeners and packages them through song lyrics that hold special meaning. This research is entitled